Do institutions matter for refugee integration? a comparison of case worker integration strategies in Switzerland and Canada - Ihssane Otmani; Giuliano Bonoli (Comparative Migration Studies)
Abstract In this paper we explore the extent to which differences in institutional settings, with a focus on the human capital formation regime, shape the integration trajectories proposed to recently- arrived refugees. To do so, we compare two countries, Switzerland and Canada, which are committed to implementing integration policy for refugees and belong to two different human capital formation regimes. We investigate whether ending up in a country with a collective skill formation system (Switzerland) limits refugee integration paths by “managing” their aspirations and directing them towards predefined options compared to a country with a more liberal human capital formation regime (Canada) where refugees may have more room of manoeuvre to fulfil their aspirations. In order to test this hypothesis, we used qualitative vignettes and compared integration paths proposed by case workers to refugees in a Swiss Canton (Vaud) and in a Canadian Province (Québec). We found that overall, the integration paths proposed are very similar, regardless of the institutional context. We reason that this largely unexpected result is due to the similarities in the overall orientation of integration policy; the similarity of the policy problem and labour market shortage in the low skill segment experienced in both countries.